Evaluation of Drug Storage Systems Based on Good Distribution Practice in Pharmaceutical Wholesalers in Indonesia: A Systematic Review - Martsom Putra Sulung S Langga; Teuku Nanda Saifullah Sulaiman; Satibi (Jurnal FARMASIMED (JFM), 2026)
The pharmaceutical distribution system plays a crucial role in ensuring that medicines maintain their quality, safety, and efficacy throughout the supply chain. In Indonesia, Pharmaceutical Wholesalers (PBF) are required to implement Good Distribution Practice (CDOB), including proper storage systems; however, variations in compliance have been reported in several local studies. Purpose: This study aimed to identify the implementation of drug storage systems in PBF in Indonesia based on CDOB and to analyze the most frequent areas of non-compliance. Methods: A systematic review was conducted following PRISMA 2020 guidelines. Literature searches were performed in Google Scholar and Semantic Scholar for studies published between 2014 and 2024. Primary observational descriptive studies focusing on drug storage practices in Indonesian PBF were included, and seven eligible articles were analyzed. Result: The findings indicate that non-compliance most frequently occurs in the operational aspect, particularly in the inconsistent implementation of FEFO, medicines classification, and adherence to standard operating procedures. Issues related to building and equipment, such as unstable temperature control and inadequate ventilation, are also commonly reported. Weaknesses in documentation, stock verification, and managerial oversight further affect storage effectiveness. Conclusion: These recurring patterns suggest that challenges lie more in implementation consistency and internal control rather than regulatory absence. Overall, drug storage practices in Indonesian PBF generally refer to CDOB standards; however, compliance remains uneven. Strengthening operational discipline, documentation accuracy, and managerial supervision is essential to improve distribution quality and ensure patient safety.